Embedding digital transformation in South African higher education through bridging the digital divide: a university case study - Mutakwa, Darlington; Muloiwa-Klenam, Takalani (African Perspectives of Research in Teaching and Learning Journal (APORTAL), 2025)
South Africa’s intricate colonial legacy has significantly influenced and entrenched profound socio-economic divides across its populace. In the higher education sector, the adoption of digital technologies has been markedly uneven, mirroring the historical socio-economic gap. The COVID-19 pandemic uniquely drew attention to this digital divide, underscoring the critical need for comprehensive digital transformation strategies. Leveraging insights gained during the pandemic, this study advocates for deliberate efforts to bridge the digital divide, aspiring towards a digitally transformed landscape in South African higher education. This study is anchored in an annual university undergraduate student experience survey, where 10,943 respondents voluntarily participated. A total of 10 items related to experience in using digital technology were purposively included in this study. The study used quantitative and qualitative data collected in the survey. In addition, five purposively sampled key informant interviews were conducted with academic and support staff working in digital transformation within the university. Overall, this study showcases the persistent gaps in digital transformation at the university. Recommendations to narrow the digital divide and promote a digitally transformed higher education are suggested.
Journal article published in African Perspectives of Research in Teaching and Learning Journal Issue 6, Volume 9, 2025
Keywords: Digital divide; Digital technology; Digital transformation; Higher education; Learning and teaching; Student experience; COVID-19; Education higher, South Africa; Technological innovations; Education, Higher -- Effect of technological innovations on; Internet in higher education